Faktor-Faktor Yang Mempengaruhi Immersion Saat Live Streaming Syaria Shopping Serta Pengaruhnya Kepada Minat Pembelian (Studi Pada Social Commerce Tik Tok Indonesia) - Shabira Maharani; I Made Bayu Dirgantara (Jurnal Ilmiah Ekonomi Islam, 2023)
The mainstay platform in Indonesia in terms of online shopping today is e-commerce. The population specified in writing this research is people in Indonesia who have watched a live streaming shopping program on the social commerce platform TikTok for more than 3 minutes in the past month and have interacted with the streamer. The sample that will be used by researchers in this research is 150 respondents who in the past month have watched live streaming shopping on the TikTok platform for more than 3 minutes and have interacted with the streamer. This study shows that the results of all the hypotheses proposed in this study have a positive and significant effect. H1: Visibility has a significant effect on immersion. H2: Metavoicing has a significant effect on immersion. H3: Shopping guides have a significant effect on immersion. H4: Trade affordability has a significant effect on immersion. H5: Immersion has a significant effect on purchase intention. H6: Immersion mediates the relationship between visibility and purchase intention. H7: Immersion mediates the relationship between metavoicing and purchase intention. H8: Immersion mediates the relationship between shopping guides and purchase intention. H9: Immersion mediates the relationship between trade affordability and purchase intention.